(Non-)Determining the Original Speaker: Reportative Particles versus Verbs - Zubeldia, Larraitz (Research in Language, 2013)
This work argues that the Basque reportative particle omen contributes to the propositional contents of the utterance, and it is not an illocutionary force indicator, contrary to what seems to be suggested by the standard view on omen. The results of the application of the assent/dissent test for the case of omen show that subjects not only accept a rejection of the reported content (p), but also a rejection of the evidential content (pomen) itself. The results are similar to those of the verb esan ‘to say’. It is, then, proposed that the difference between these two elements can be explained by distinguishing between the contents of the utterances (with Korta & Perry 2007, 2011), regarding the (non-)articulation of the original speaker.